General Equilibrium Effects of Price Distortions on Global Markets, Farm Incomes and Welfare - Valenzuela, Ernesto; van der Mensbrugghe, Dominique; Anderson, Kym (World Bank, Washington, DC, 2017)
Earnings from farming in many developing countries have been depressed by a pro-urban bias in own-country policies as well as by governments of richer countries favoring their farmers with import barriers and subsidies. Both sets of policies, which reduce national and global economic welfare and contribute to global inequality and poverty, have been undergoing reform since the 1980s. Using the linkage model of the global economy and modifications to the pre-release of version 7 of the Global Trade Analysis Project (GTAP) protection database for 2004, this paper seeks to compare the effect of those reforms to date with those that would come from removing remaining agricultural and trade policies. Two sets of results are thus presented: one showing the effects of policy reforms between 1980-84 and 2004, the other showing what the removal of remaining distortions as of 2004 could be. Both sets of results indicate improvements in the real value of agricultural output and exports, the real returns to farm land and unskilled labor, and real net farm incomes in most developing country regions despite the adverse effect on the international terms of trade for some developing countries that are net food importers or are enjoying preferential access to agricultural markets of high-income countries. Landowners in those high-income countries still offering their farmers price supports could readily afford to compensate them from the benefits of removing remaining agricultural protectionism.